Atlantoaxial Instability in Down Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
Results of an investigation of 130 children with Down syndrome screened for atlantoaxial instability are reported from Our Lady's Hospital for Sick Children, Crumlin, Dublin, Ireland.